The Pan-African Women's Ecumenical Empowerment Network in the Caribbean - Ortega Suárez, Ofelia (The ecumenical review, 2019)
The context of theological formation in the Caribbean is the diversity and crucible of cultures and in which women have played a great role and made a great impact.